The Quality of Working Conditions in Rural Areas in the Opinion of Workers and Their Superiors Using the Example Wood Processing Plants (Case Study) - Polek-Duraj, Kornelia (Olsztyn Economic Journal, 2018)
The article attempts to characterize working conditions in wood processing plants located in the rural areas of the Opole region, taking into account the opinion of employees and their supervisors. The analysis of working conditions was made on the basis of key factors. Particular attention was paid to organizational and technical as well as to economic working conditions. The first area is focused on the factors of the work environment and work organization, while the second area is focused on employment conditions.